Science teacher mentors’ perceptions of actual and preferred school conditions for mentoring student teachers to effectively use learning technology - Matorevhu, Alois (SAINTIS Publishing, 2022)
In Zimbabwe teachers’ colleges diploma in science education student teachers go for Attachment Teaching Practice (ATP) in the second year of the three year diploma. Among others during ATP, science teacher mentors assist student teachers to develop skills in using instruction anchored on learning technology This study sought to find out the nature of science teacher mentors’ perceptions of actual and preferred school conditions involved in mentoring student teachers to effectively use learning technology A questionnaire was used to collect both qualitative and quantitative data. Results indicate that school conditions like high workload, large classes, congested timetables, lack of learning/teaching resources and nature of appraisal system, reduce effectiveness, of mentoring, hence compromising the quality of science teacher preparation. The potential of science teacher mentors could be enhanced by creating an enabling work environment, through meeting mentor needs.